1)Al2O3 + 6HCl = 2AlCl3 + 3H2O
Al2O3 + 6H(+) + 6Cl(-) = 2Al(+3) + 6Cl(-) + 3H2O
Al2O3 + 6H(+) = 2Al(+3) + 3H2O
2) Ba(NO3)2 + K2CO3 = BaCO3 + 2KNO3
Ba(+2) + 2NO3(-) + 2K(+) + CO3(-2) = BaCO3 + 2K(+) + 2NO3(-)
Ba(+2) + CO3(-2) = BaCO3
3) 3K2CO3 + 2H3PO4 =2 K3PO4 +3 CO2 + 3H2O
6K(+) + 3CO3(-2) + 6H(+) + 2PO4(-3) = 6K(+) + 2PO4(-3) + 3CO2 + 3H2O
3CO3(-2) + 6H(+) = 3CO2 + 3H2O
4) H3PO4 +3 KOH = K3PO4 +3 H2O
3H(+) + PO4(-3) + 3K(+) + 3OH(-) = 3K(+) + PO4(-3) + 3H2O
3H(+) + 3OH(-) = 3H2O
5) K2CO3 + BaCl2 = BaCO3 + 2KCl
2K(+) + CO3(-2) + Ba(+2) + 2Cl(-) = BaCO3 + 2K(+) + 2Cl(-)
Ba(+2) + CO3(-2) = BaCO3
1)Al2O3 + 6HCl = 2AlCl3 + 3H2O
Al2O3 + 6H(+) + 6Cl(-) = 2Al(+3) + 6Cl(-) + 3H2O
Al2O3 + 6H(+) = 2Al(+3) + 3H2O
2) Ba(NO3)2 + K2CO3 = BaCO3 + 2KNO3
Ba(+2) + 2NO3(-) + 2K(+) + CO3(-2) = BaCO3 + 2K(+) + 2NO3(-)
Ba(+2) + CO3(-2) = BaCO3
3) 3K2CO3 + 2H3PO4 =2 K3PO4 +3 CO2 + 3H2O
6K(+) + 3CO3(-2) + 6H(+) + 2PO4(-3) = 6K(+) + 2PO4(-3) + 3CO2 + 3H2O
3CO3(-2) + 6H(+) = 3CO2 + 3H2O
4) H3PO4 +3 KOH = K3PO4 +3 H2O
3H(+) + PO4(-3) + 3K(+) + 3OH(-) = 3K(+) + PO4(-3) + 3H2O
3H(+) + 3OH(-) = 3H2O
5) K2CO3 + BaCl2 = BaCO3 + 2KCl
2K(+) + CO3(-2) + Ba(+2) + 2Cl(-) = BaCO3 + 2K(+) + 2Cl(-)
Ba(+2) + CO3(-2) = BaCO3
H2+H2O=
2H2+O2=2H2O
H2+N2a=2NAH
H2+H2=
H2+CuO=CU+ H2O
H2+CaO=CA +H2O
S+H2O=SO2 +H2
S+O2=SO2
S+Na=NA2S
S+H2=SH2
2S+2CuO=2CU+SO2
S+2CaO=2CA + SO2